Antibody 27F3 Broadly Targets Influenza A Group 1 and 2 Hemagglutinins through a Further Variation in VH1-69 Antibody Orientation on the HA Stem - Lang, Shanshan; Xie, Jia; Zhu, Xueyong; Wu, Nicholas C.; Lerner, Richard A.; Wilson, Ian A. (Cell reports (Cambridge), 2017)
Antibodies that target both group 1 and group 2 influenza A viruses are valuable for therapeutic and vaccine development, but only a few have been reported to date. Here, we describe a new VH1-69 antibody 27F3 that broadly recognizes heterosubtypic hemagglutinins (HAs) from both group 1 and group 2 influenza A viruses. Structural characterization of 27F3 Fab with A/California/04/2009 (H1N1) hemagglutinin illustrates that 27F3 shares the key binding features observed in other VH1-69 antibodies to the HA stem. Compared to other VH1-69 antibodies, the 27F3 VH domain interacts with the HA stem in a distinct orientation, which alters its epitope and may have influenced its breadth. The diverse rotations of VH1-69 antibodies on the HA stem epitope highlight the different ways that this antibody family can evolve to broadly neutralize influenza A viruses. These results have important implications for understanding how to elicit broad antibody responses against influenza virus. [Display omitted] •Antibody 27F3 was isolated from a human combinatorial scFv phage display library•27F3 targets most group 1 and group 2 influenza A viruses•27F3 possesses the IFY motif, the signature of VH1-69 antibodies that bind the HA stem•Variable VH1-69 VH orientations on the HA stem evolve via distinct somatic mutations Lang et al. discover a human VH1-69 antibody that neutralizes group 1 and group 2 influenza A viruses and demonstrate the consensus and differences in the mode of binding of antibodies from this class with the HA stem.